The influence of leadership and financial performance on business sustainability in microfinance institutions - Maharani, Ida Ayu Dinda Priyanka; Wiagustini, Ni Luh Putu; Baskara, I Gde Kajeng; Rahyuda, Henny (International Journal Labs, 2024)
Microfinance institutions (MFIs) play a pivotal role in empowering marginalized communities by providing them with crucial financial services. The sustainability of these institutions is essential to ensure a sustained positive impact on the lives of the underserved. To explore the factors influencing MFI sustainability, this study conducts a systematic literature review of relevant articles published between 2015 and 2023, focusing on the roles of leadership and financial performance. The findings of the study reveal a compelling positive correlation between effective leadership and financial performance with MFI sustainability. A strong and visionary leadership within MFIs is found to foster a robust organizational culture, articulate a clear vision, motivate employees, and effectively manage risks. These leadership qualities, in turn, contribute significantly to improved financial outcomes for the institution. Conversely, the study highlights the integral role of strong financial performance in ensuring MFI sustainability. A well-performing financial structure not only instills trust among customers but also facilitates business growth and secures vital profits. These financial strengths are crucial pillars that fortify the overall sustainability of MFIs, enabling them to continue their mission of empowering marginalized communities. In conclusion, this study underscores the critical interplay between leadership and financial performance in driving MFI sustainability. The recommendations derived from the findings emphasize the importance of investing in leadership development within MFIs and implementing robust financial practices.